Pengaruh Penggunaan Lembar Kerja Siswa Terhadap Hasil Belajar Tematik Tema Cita-Citaku Pada Siswa Kelas IV SDN 104266 Pematang Sijonam - Rizka Ramadhani; Sujarwo (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2023)
This study aims to analyze the effect of using student worksheets (LKS) on student learning outcomes on the theme "My dreams" in grade IV SDN 104266 Pematang Sijonam. The experimental method was used with an experimental class that used LKS and a control class that did not use LKS. Student learning outcomes were measured through pretests and posttests, and normality tests, homogeneity of variance tests, and pair tests were conducted for statistical analysis. From the results of the analysis, it was found that initially the experimental and control classes did not reach the Minimum Completion Criteria (KKM) in the pretest. However, after the treatment in the form of using the LKS was given only to the experimental class, both classes reached the KKM in the posttest. The posttest results showed that the experimental class that used the worksheet obtained a higher total score and a higher average compared to the control class that did not receive the treatment.The normality test showed that all data, both pretests and posttests from the experimental and control classes, had a normal distribution. The homogeneity of variance test showed that there was no significant difference in data variability between the two groups, indicating the homogeneity of variance required for the independent sample t-test. The paired test results showed that there was a significant difference between the pretests and posttests in both groups. This confirms that the use of LKS has a significant positive effect on students' learning outcomes. Based on these findings, it can be concluded that the use of student worksheets (LKS) is effective in improving student learning outcomes on the theme "My dreams" in class IV of SDN 104266 Pematang Sijonam. This study provides empirical support for implementing the use of LKS in learning and suggests implementation strategies that are effective in improving student learning outcomes.